Porous bodies and methods for manufacturing porous bodies

CN117881729BActive Publication Date: 2026-10-27MURATA MFG CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202280059183.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-29
Filing Date
2022-10-26
Publication Date
2026-10-27
Estimated Expiration
2042-10-26

AI Technical Summary

Benefits of technology

[0021]根据本公开,可以使用微细的纤维的LCP提供强度高的多孔体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117881729B_ABST
    Figure CN117881729B_ABST
Patent Text Reader

Abstract

A porous body comprising liquid crystal polymer powder, wherein the liquid crystal polymer powder comprises fibrous particles composed of liquid crystal polymer, the average diameter of the fibrous particles composed of liquid crystal polymer being 2 μm or less, and the porous body having an average pore size of 10 μm or less as determined by mercury porosimetry, and having a density of 25 N / mm². 2 The above tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to porous bodies and methods for manufacturing porous bodies. Background Technology

[0002] Generally, porous polymers include fiber-based nonwoven fabrics and porous membranes based on membrane manufacturing methods (Patent Documents 1 to 7). Furthermore, when forming porous polymers using liquid crystal polymers (LCPs), even when using fibers obtained through conventional melt spinning to form nonwoven fabrics, only porous bodies with coarse fiber diameters and large pores can be formed. Therefore, to form porous bodies with fine pores, it is necessary to use LCPs with fine fibers.

[0003] Methods for forming nonwoven fabrics using LCP with fine fibers include papermaking and meltblowing. Methods for forming porous membranes include stretching LCP membranes with added fillers and phase separation.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-129392

[0007] Patent Document 2: Japanese Patent Application Publication No. 2000-119952

[0008] Patent Document 3: Japanese Patent Application Publication No. 2003-26866

[0009] Patent Document 4: Japanese Patent Application Publication No. 2005-120535

[0010] Patent Document 5: Japanese Patent Application Publication No. 2002-61063

[0011] Patent Document 6: Japanese Patent Application Publication No. 2017-514315

[0012] Patent Document 7: Japanese Patent Application Publication No. 2012-224692 Summary of the Invention

[0013] However, when forming nonwoven fabrics using the papermaking method, there are problems such as the inability to use them at high temperatures, the crushing of porous structures, and weak strength. Furthermore, when forming nonwoven fabrics using the meltblown method, there are issues such as: the melt viscosity is highly temperature-dependent, and even slight temperature fluctuations can alter the fluidity, thus requiring formation within a narrow temperature range.

[0014] When forming porous membranes by stretching LCP membranes with added fillers, only membranes with small through-pores can be formed, not dense porous bodies. Furthermore, when forming porous membranes by phase separation, only LCPs dissolved in solvents can be used.

[0015] In view of the above-mentioned problems, the present disclosure aims to provide a high-strength porous body using LCP with fine fibers.

[0016] The porous body disclosed herein is a porous body comprising liquid crystal polymer powder, wherein...

[0017] The aforementioned liquid crystal polymer powder comprises fibrous particles composed of liquid crystal polymers.

[0018] The average diameter of the aforementioned fibrous particles composed of liquid crystal polymers is less than 2 μm.

[0019] The aforementioned porous material has an average pore size of less than 10 μm, as determined by mercury porosimetry.

[0020] With 25N / mm 2 The above tensile strength.

[0021] According to this disclosure, high-strength porous bodies can be provided using LCP with fine fibers. Attached Figure Description

[0022] Figure 1 It is a coordinate graph showing the relationship between heating temperature and tensile strength in the heating process of Examples 1-3 and Comparative Example 1.

[0023] Figure 2 This is a graph showing the relationship between heating temperature and tensile strength in the heating process of Examples 4-6 and Comparative Example 2.

[0024] Figure 3 The photograph is a cross-section of the porous body of Example 1.

[0025] Figure 4 The photograph is a cross-section of the porous body of Example 2.

[0026] Figure 5 The photograph is a cross-section of the porous body in Example 3.

[0027] Figure 6 The photograph was taken from the cross-section of the porous body in Comparative Example 1.

[0028] Figure 7 The photograph was taken from the cross-section of the porous body in Reference Example 1.

[0029] Figure 8 The photograph is a cross-section of the porous body in Example 7.

[0030] Figure 9 This is a flowchart illustrating the manufacturing process of the porous body in Embodiment 1.

[0031] Figure 10 This is a flowchart illustrating the manufacturing process of the porous body in Embodiment 2. Detailed Implementation

[0032] The following describes the embodiments of this disclosure, but this disclosure is not limited thereto.

[0033] [Implementation Method 1]

[0034] <Porous body>

[0035] The porous body of this embodiment comprises liquid crystal polymer powder (LCP powder), which includes fibrous particles (liquid crystal polymer fibers: LCP fibers) composed of liquid crystal polymers, wherein the average diameter of the LCP fibers is 2 μm or less. The porous body has an average pore size of 10 μm or less as measured by mercury porosimetry and a strength of 25 N / mm². 2 The above tensile strength.

[0036] (Liquid crystal polymer powder)

[0037] There is no particular limitation as to liquid crystal polymers; for example, thermotropic liquid crystal polymers can be cited. Thermotropic liquid crystal polymers refer to aromatic polyesters synthesized mainly from monomers such as aromatic diols, aromatic dicarboxylic acids, and aromatic hydroxycarboxylic acids, which exhibit liquid crystal properties when molten.

[0038] Liquid crystal polymer molecules have a negative coefficient of linear expansion (CTE) along the molecular axis and a positive CTE in the radial direction of the molecular axis.

[0039] The liquid crystal polymer preferably does not have amide bonds. Examples of thermotropic liquid crystal polymers without amide bonds include copolymers of p-hydroxybenzoic acid, terephthalic acid, and dihydroxybiphenyl (copolymers of p-hydroxybenzoic acid and ethylene terephthalate) with high melting points and low CTEs, referred to as type I liquid crystal polymers, or copolymers of p-hydroxybenzoic acid and 2,6-hydroxynaphthoic acid with melting points between type I and type II liquid crystal polymers, referred to as type 1.5 (or type III).

[0040] The LCP fibers contained in LCP powder are not particularly limited as long as they contain fibrous portions. The fibrous portions can be linear or branched, etc.

[0041] The average diameter of the LCP fibers is 2 μm or less, preferably 1 μm or less. Furthermore, the average aspect ratio of the LCP fibers is preferably 10 to 500, more preferably 10 to 300.

[0042] It should be noted that the average diameter and average aspect ratio of LCP fibers were determined by the following methods.

[0043] LCP powder, consisting of LCP fibers to be measured, was dispersed in ethanol to prepare a slurry containing 0.01% by mass of LCP powder. The slurry was prepared such that the water content was 1% by mass or less. Then, 5–10 μL of the slurry was dropped onto a glass slide, and the slide was allowed to dry naturally. By allowing the slurry to dry naturally, LCP powder was deposited on the glass slide.

[0044] Next, image data of more than 100 particles (LCP fibers) constituting the LCP powder were acquired by observing a designated area of ​​LCP powder placed on a glass slide using a scanning electron microscope (SEM). It should be noted that during image data acquisition, the area was defined according to the size of each LCP particle to ensure that the number of image data was more than 100. Furthermore, to suppress omissions or measurement errors in image data acquisition for each LCP particle, the SEM magnification was appropriately changed to 500x, 3000x, or 10000x while acquiring the aforementioned image data.

[0045] Next, using the image data obtained above, the longitudinal and width dimensions of each LCP fiber were measured.

[0046] In an LCP fiber captured by the aforementioned image data, the direction of the straight line connecting the two ends of the longest path along the path from one end through approximately the center of the particle to the opposite end is defined as the long-side direction. Then, the length of the straight line connecting the two ends of the longest path is measured as the long-side direction dimension.

[0047] In addition, the particle size in a direction orthogonal to the long side direction was measured at three different locations along the aforementioned long side direction of a single LCP powder particle. The average value of the dimensions measured at these three locations was taken as the width direction dimension (fiber diameter) of each LCP powder particle.

[0048] Then, the ratio of the longitudinal dimension to the fiber diameter (longitudinal dimension / fiber diameter) is calculated as the aspect ratio of the LCP fiber.

[0049] Then, the average fiber diameter measured from 100 LCP fibers was taken as the average diameter.

[0050] In addition, the average aspect ratio of 100 LCP fibers was used as the mean aspect ratio.

[0051] It should be noted that the aforementioned fibrous particles can be contained in LCP powder as aggregates of fibrous particles.

[0052] Furthermore, the aforementioned fibrous particles tend to have the axial direction of the LCP molecules constituting the fibrous particles aligned with the long side direction of the fibrous particles. This is believed to be because, during the manufacture of LCP powder, the multiple structural domains formed by the bundled LCP molecules disrupt each other, thereby aligning the axial direction of the LCP molecules along the long side direction of the fibrous particles.

[0053] In LCP powder, the content (number ratio) of particles other than fibrous particles (substantially unfibrillated block particles) is preferably 20% or less. For example, when LCP powder is placed on a plane, particles with a maximum height of 10 μm or less are fibrous particles, and particles with a maximum height of more than 10 μm are block particles.

[0054] The D50 (average particle size) value of LCP powder, determined by particle size analysis using a laser diffraction scattering method and a particle size distribution measuring device, is preferably 13 μm or less.

[0055] (Average aperture)

[0056] The porous body of this embodiment has an average pore size of 10 μm or less. Here, "average pore size" refers to the pore size in which the cumulative pore distribution, as measured by mercury porosimetry, accounts for 50% of the total pore volume. When the average pore size of the porous body exceeds 10 μm, it may be impossible to fully obtain the functions of the porous body, such as filtration performance. The average pore size of the porous body is preferably 5.0 μm or less. Alternatively, the average pore size of the porous body can be 0.1 μm or more, or 0.3 μm or more.

[0057] (Tensile strength)

[0058] The porous body in this embodiment has a strength of 25 N / mm². 2 The above tensile strength. In this embodiment, the tensile strength refers to the value obtained by dividing the load at which the test piece is cut (excluding the hollow portion) by the cross-sectional area (N / mm²) when a 5mm × 25mm test piece taken from the porous body is stretched under conditions of a clamping interval of 13mm and a stretching speed of 0.6mm / min. 2 This specification allows for comparison of tensile strength values ​​of porous materials with different film thicknesses, regardless of the film thickness. The preferred tensile strength of the porous material is 40 N / mm². 2 The above, more preferably 60 N / mm 2 above.

[0059] (Additives)

[0060] The porous body of this embodiment may contain additives. By including additives in the porous body, the porous body can be endowed with the functions of the additives, such as water resistance, oil resistance, and heat dissipation. Examples of additives include inorganic fillers, polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), carbon micropowder, carbon microfiber, metal powder, and nitride powder. Examples of nitride powders include boron nitride powder, aluminum nitride powder, and silicon nitride powder.

[0061] Furthermore, the porous body of this embodiment does not contain an adhesive for bonding the LCP fibers together. This is because the porous body of this embodiment achieves the aforementioned tensile strength by heating the LCP fibers to bond them together. Additionally, the inclusion of an adhesive carries the risk of reduced heat resistance or increased water absorption.

[0062] <Method for manufacturing porous materials>

[0063] The following describes each step of the manufacturing method of this embodiment.

[0064] like Figure 9 As shown, the porous body manufacturing method of this embodiment includes a dispersion step (S1), a felting step (S2), and a heating step (S3).

[0065] First, the method for producing the LCP powder used in the dispersion step (S1) will be described in detail. This LCP powder can be produced, for example, by sequentially performing the following coarse grinding step, fine grinding step, coarse particle removal step, and fiberization step.

[0066] Examples of the shapes of LCP raw materials used in the production of LCP powder include uniaxially oriented particles, biaxially oriented films, and powdered LCP. The LCP constituting the LCP raw material is the same as the LCP constituting the aforementioned LCP fibers.

[0067] (Coarse grinding process)

[0068] In the coarse grinding process, the LCP raw material is coarsely ground. For example, the LCP raw material is coarsely ground using a milling machine. The size of the coarsely ground LCP particles is not particularly limited as long as they can be used as raw materials for the micro-grinding process described later. The maximum particle size of the coarsely ground LCP particles is, for example, 3 mm or less.

[0069] It should be noted that a coarse grinding process is not necessarily required. For example, if the LCP raw material can be used as a raw material for the micro-grinding process, it can be used directly as a raw material for the direct micro-grinding process.

[0070] (Micro-pulverization process)

[0071] In the micronization process, the LCP raw material (after the coarse pulverization process) is pulverized while dispersed in liquid nitrogen to obtain granular micronized liquid crystal polymer (micronized LCP).

[0072] In the micronization process, it is preferable to use a medium to pulverize the LCP raw material dispersed in liquid nitrogen. The medium is, for example, beads. From the viewpoint of handling liquid nitrogen, a bead mill, which presents fewer technical problems, is preferred in the micronization process of this embodiment. For example, the liquid nitrogen bead mill "LNM-08" manufactured by IMEX Corporation can be cited as an example of an apparatus suitable for the micronization process.

[0073] The granular micronized LCP obtained through the micronization process preferably has a D50 of less than 50 μm, as measured by a particle size distribution measuring device based on laser diffraction scattering. This prevents the granular micronized LCP from clogging the nozzle during the fiberization process described below.

[0074] (Coarse particle removal process)

[0075] Next, in the coarse particle removal step, coarse particles are removed from the granular micronized LCP obtained in the above-mentioned micronization step. For example, by sieving the granular micronized LCP through a sieve, the granular micronized LCP that passes through the sieve is obtained, and the granular LCP that remains on the sieve is removed, thereby removing the coarse particles contained in the granular micronized LCP. The type of sieve can be appropriately selected; for example, a sieve with a mesh size of 53 μm can be used. It should be noted that a coarse particle removal step is not necessarily required.

[0076] (Fiberization process)

[0077] Next, in the fiberization process, the granular LCP is crushed using a wet high-pressure crushing device to obtain LCP powder. In the fiberization process, the micronized LCP is first dispersed in a dispersion medium used in the fiberization process. The dispersed micronized LCP may not have coarse particles removed, but it is preferable to remove them. Examples of dispersion media used in the fiberization process include water, ethanol, methanol, isopropanol, toluene, benzene, xylene, phenol, acetone, methyl ethyl ketone, diethyl ether, dimethyl ether, hexane, or mixtures thereof.

[0078] Then, the micronized LCP, in a state of dispersion medium used in the fiberization process, i.e., a paste or slurry-like micronized LCP, is passed through a nozzle under high pressure. By passing through the nozzle under high pressure, the shear force or impact energy generated by the high-speed flow within the nozzle acts on the LCP, causing the granular micronized LCP to break down, thereby fiberizing the LCP and obtaining LCP powder composed of fine LCP fibers. From the viewpoint of providing high shear force or high impact energy, it is preferable to minimize the nozzle diameter as much as possible to prevent clogging of the micronized LCP in the nozzle. Since the granular micronized LCP has a small particle size, the nozzle diameter of the wet high-pressure crushing device used in the fiberization process can be reduced. For example, the nozzle diameter is 0.2 mm or less.

[0079] It should be noted that, as described above, multiple microcracks are formed in the granular micro-pulverized LCP. Therefore, by pressurizing the wet high-pressure crushing device, the dispersion medium penetrates into the interior of the micro-pulverized LCP through the microcracks. Then, when the paste-like or slurry-like micro-pulverized LCP passes through the nozzle at atmospheric pressure, the dispersion medium that has penetrated into the interior of the micro-pulverized LCP expands within a short period of time. Through the expansion of the dispersion medium that has penetrated into the interior of the micro-pulverized LCP, it breaks down from the interior of the micro-pulverized LCP. Therefore, fiberization proceeds to the interior of the micro-pulverized LCP, and the LCP molecules separate into structural domain units arranged in a unidirectional manner. Thus, in the fiberization process of this embodiment, by defibrating the granular micro-pulverized LCP obtained in the micro-pulverization process of this embodiment, an LCP powder with a lower content of block particles and composed of fine LCP fibers can be obtained compared to the LCP powder obtained by crushing granular LCP obtained by conventional cryogenic pulverization methods.

[0080] It should be noted that in the fiberization process of this embodiment, the micronized LCP can be crushed multiple times using a wet high-pressure crushing device to obtain LCP powder. However, from the viewpoint of manufacturing efficiency, it is preferable to crush the LCP multiple times using a wet high-pressure crushing device, for example, less than 5 times.

[0081] (Dispersed process: S1)

[0082] In the dispersion step, the initial step in the method for manufacturing porous materials, the LCP powder is dispersed in a dispersion medium to form a paste or slurry. Thus, in this embodiment, since the aforementioned fine fibrous LCP powder is used, it is possible to disperse the LCP powder in a high-viscosity dispersion medium.

[0083] Examples of dispersion media used in the dispersion process include butanediol, water, ethanol, terpineol, and mixtures of water and ethanol. For instance, when butanediol is used as the dispersion medium, a paste-like LCP powder is obtained. When a mixture of water and ethanol is used as the dispersion medium, a slurry-like LCP powder is obtained.

[0084] In addition, when manufacturing porous bodies containing additives, a paste or slurry-like mixture of LCP powder and additives is obtained by mixing LCP powder and additives in this process (hereinafter, the mixture of LCP powder and additives is sometimes referred to as "mixture"). The mixing ratio of additives relative to the mixture is preferably 50% by volume or less.

[0085] (Felting process: S2)

[0086] Next, in the felting process, the paste or slurry-like LCP powder or mixture is dried to form liquid crystal polymer fiber felt (LCP fiber felt). In this embodiment, the felting process is, for example, a papermaking process. In the papermaking process, the dispersion medium used in the dispersion process can be easily recovered and reused, and porous bodies can be manufactured inexpensively.

[0087] In the felting process using the papermaking method, specifically, LCP powder or mixture in slurry form is first formed on a sieve, a nonwoven microporous sheet, or a fabric. Then, the slurry-like LCP powder or mixture placed on the sieve is heated and dried to obtain LCP fiber felt.

[0088] In the felting process of this embodiment, the papermaking method described above can be replaced, and the paste-like LCP powder or mixture can be formed into LCP fiber felt through a coating process and a drying process.

[0089] In the coating process, a paste-like LCP powder or mixture is applied to a substrate. Here, "substrate" refers to the material or support material used to coat the paste-like LCP powder or mixture, such as metal foils like copper foil, polyimide films, PTFE films, or composite sheets made of reinforcing materials such as carbon fibers or glass fibers and heat-resistant resins.

[0090] Next, the paste-like LCP powder or mixture coated on the substrate is heated and dried through a drying process, thereby vaporizing the dispersion medium. Through the above-mentioned heating and drying, an LCP fiber mat is formed on the substrate.

[0091] Furthermore, during the drying process, the overall thickness of the LCP powder or mixture gradually decreases as the dispersion medium is slowly removed from the paste-like LCP powder or mixture. Therefore, the thickness of the LCP fiber mat is thinner than the overall thickness of the LCP powder or mixture formed on the product.

[0092] Furthermore, as the overall thickness of the paste-like LCP powder or mixture gradually decreases during drying, the orientation of the long side direction of the fibrous particles in the LCP powder changes. Specifically, among the fibrous particles, those with a long side direction in the overall thickness direction of the paste-like LCP powder or mixture are inclined inwards toward the main surface of the substrate. Therefore, the long side direction of the fibrous particles in the formed LCP fiber mat is anisotropic.

[0093] In the aforementioned felting process, after further coating a paste-like LCP powder or mixture onto the LCP fiber felt formed on the substrate through the drying process, the dispersion medium can be vaporized by drying it. Thus, the coating and drying processes can be repeated sequentially in the aforementioned felting process. This allows for the acquisition of LCP fiber felt with a desired weight per unit area. Furthermore, when repeating the coating and drying processes, a mixture in which the mixing ratio of LCP powder and additives is varied for each coating process can be used. This allows for the acquisition of LCP fiber felt capable of forming a porous structure with desired properties.

[0094] (Heating process: S3)

[0095] Next, in the heating process, a porous body is obtained by heating the LCP fiber felt. Alternatively, the heating process can be performed under an inert gas atmosphere. This further improves the tensile strength of the porous body.

[0096] The heating temperature in the heating process is in the range of -60°C to -5°C, which is the melting point of the LCP powder. When the heating temperature is below -60°C, the adhesion between the LCP fibers is weak, and a porous body with practical strength cannot be obtained. When the heating temperature is above -5°C, which is the melting point of the LCP powder, the LCP fibers soften and deform, thus failing to maintain the porous structure. The heating temperature is preferably in the range of -50°C to -10°C, which is the melting point of the LCP powder, and more preferably in the range of -40°C to -20°C.

[0097] There are no particular limitations on the holding time during the heating process; for example, it can be 5 minutes or more, or 15 minutes or more. Furthermore, since a porous body with higher strength is formed through prolonged holding, it can be 30 minutes or more, or 60 minutes or more.

[0098] It should be noted that in the felting process, when LCP fiber felt is formed on the substrate through the coating and drying processes, the LCP fiber felt and the substrate are heated together. This allows for the inexpensive acquisition of a porous body bonded to the substrate. Alternatively, by coating a necessary portion of the substrate with a paste-like LCP powder or mixture and drying it, a porous body can be partially or three-dimensionally formed on the substrate.

[0099] [Implementation Method 2]

[0100] <Porous body>

[0101] The porous body of this embodiment has an average pore size of less than 1.0 μm, which differs from Embodiment 1. Porous bodies with fine average pore sizes are considered to have excellent strength, filtration characteristics, etc. Other than that, the same points are as in Embodiment 1, and repeated descriptions are omitted.

[0102] <Method for manufacturing porous materials>

[0103] like Figure 10 As shown, the porous body manufacturing method of this embodiment includes a dispersion step (S10), a felting step (S20), a hot pressing step (S30), and a heating step (S40). Hereinafter, each step of the manufacturing method of this embodiment will be described. It should be noted that descriptions repeated in Embodiment 1 are omitted.

[0104] (Dispersion process: S10)

[0105] In the dispersion process, a paste or slurry-like resin mixture is prepared by dispersing LCP powder and binder resin in a dispersion medium. The binder resin is mixed in the dispersion process, and film formation is carried out in the hot pressing process described later. This is expected to improve operability, such as making the processing before the fabrication of porous bodies easier.

[0106] Examples of binder resins used in the dispersion process include acrylic resins, butyral resins, and ethyl cellulose resins. Among these, acrylic resins are preferred from a decomposition point of view. The mixing ratio of the binder resin relative to the resin mixture is preferably 30% to 70% by volume. Furthermore, the average diameter of the binder resin is preferably 10 μm or less.

[0107] It should be noted that when manufacturing porous bodies containing additives, LCP powder, binder resin and additives are mixed in this process.

[0108] (Felting process: S20)

[0109] Next, in the felting process, the paste-like or slurry-like resin mixture or the resin mixture containing additives is dried to form a resin mixture felt.

[0110] (Hot pressing process: S30)

[0111] Next, in the hot pressing process, a resin mixture film is obtained by hot pressing the resin mixture felt.

[0112] The heating temperature in the hot pressing process is 20℃ to 100℃. When the heating temperature is below 20℃, the adhesive resin does not soften, making film formation difficult. When the heating temperature exceeds 100℃, the adhesive resin flows. The preferred heating temperature is 40℃ to 80℃.

[0113] The pressure during the hot pressing process is 0.3 MPa to 3.0 MPa. When the pressure is less than 0.3 MPa, the pressure is insufficient, and air bubbles remain. When the pressure exceeds 3.0 MPa, the adhesive resin flows. The preferred pressure is 0.5 MPa to 1.0 MPa.

[0114] There are no particular restrictions on the holding time during the hot pressing process; for example, it can be more than 1 minute or more than 10 minutes.

[0115] (Heating process: S40)

[0116] Next, in a heating step, at least a portion of the binder resin contained in the resin mixture film is removed by heating to obtain a porous body. The porous body may contain binder resin. The proportion of residual binder resin is adjusted by the heating temperature and holding time in the heating step.

[0117] Example

[0118] The following examples illustrate the present disclosure in more detail, but the present disclosure is not limited thereto.

[0119] Experiment 1

[0120] <Example 1>

[0121] (Manufacturing of liquid crystal polymer powder)

[0122] In Example 1, firstly, uniaxially oriented LCP particles (cylindrical particles with a diameter of 3-4 mm and a melting point of 315°C) were prepared as the LCP raw material. The LCP material was a copolymer of p-hydroxybenzoic acid and 4,6-hydroxynaphthoic acid.

[0123] The LCP raw material was coarsely ground using a milling machine (IKA, MF10). The coarsely ground LCP was obtained by passing the coarsely ground LCP through a 3mm diameter screen located at the outlet of the milling machine.

[0124] Next, the coarsely ground LCP was finely ground using a liquid nitrogen bead mill (IMEX, LNM-08, container capacity: 0.8L). Specifically, 500 mL of media and 30 g of coarsely ground LCP were added to the container and ground at 2000 rpm for 120 minutes. Zirconia (ZrO2) beads with a diameter of 5 mm were used as the media. It should be noted that the wet grinding process was performed in the liquid nitrogen bead mill with the coarsely ground LCP dispersed in liquid nitrogen. Thus, by grinding the coarsely ground LCP using a liquid nitrogen bead mill, granular, finely ground LCP was obtained.

[0125] The particle size of the micronized LCP was determined. For particle size determination, the micronized LCP dispersed in the dispersion medium was subjected to ultrasonic treatment for 10 seconds, and then the particle size was measured using a particle size distribution measuring device based on laser diffraction scattering (Horiba Manufacturing Co., Ltd., LA-950). It should be noted that the dispersion medium was a mixed solvent, ENEKIN (registered trademark, JAPAN ALCOHOL TRADING CO.,LTD.), with ethanol as the main component. The measured D50 value of the micronized LCP was 23 μm.

[0126] Next, the dispersion of micronized LCP in ENEKIN was sieved through a 53 μm mesh to remove coarse particles from the micronized LCP, while recovering the micronized LCP that passed through the sieve. The yield of micronized LCP obtained by removing these coarse particles was 85% by mass.

[0127] Next, the micronized LCP, from which coarse particles have been removed, was dispersed in a 20% (w / w) aqueous ethanol solution. Using a wet high-pressure crushing apparatus, the ethanol slurry containing the micronized LCP was repeatedly crushed five times under a nozzle diameter of 0.2 mm and a pressure of 200 MPa, thereby achieving fiberization. A high-pressure disperser (Nanovator, manufactured by Yoshida Machinery Kogyo Co., Ltd.) was used as the wet high-pressure crushing apparatus. The ethanol slurry containing the micronized LCP was dried using a spray dryer to obtain LCP powder. The average diameter of 100 LCP fibers contained in the LCP powder was measured to be 0.8 μm.

[0128] (Manufacturing of porous materials)

[0129] The LCP powder obtained above is dispersed in a 50% by mass aqueous solution of ethanol as the dispersion medium to form a slurry.

[0130] Next, using a square sheet machine (manufactured by Kumagai Riki Kogyo Co., Ltd.), the slurry-like LCP powder was spread onto a polyester microfiber nonwoven fabric (weight per unit area: 14g / m²) placed on an 80-mesh metal mesh. 2The LCP fiber mat is obtained by papermaking on top of the LCP powder. The amount of LCP powder is adjusted so that the unit area weight of the LCP fiber mat is 35 g / m². 2 Then, the LCP fiber felt is dried using a hot air dryer and peeled off from the polyester microfiber nonwoven fabric to form the LCP fiber felt.

[0131] Next, the LCP fiber felt was placed in a stainless steel drum and heated in a hot air-type non-oxidizing oven (JTEKT THERMOSYSTEM CORPORATION, inert gas oven INH-21CD). Specifically, it was heated at 260°C for 60 minutes under a nitrogen flow. This yielded a porous material.

[0132] <Examples 2-3, Comparative Example 1>

[0133] In Examples 2-3 and Comparative Example 1, the heating temperatures of the hot air-type non-oxidizing oven were 270°C, 280°C, and 250°C, respectively. All other aspects were performed in the same manner as in Example 1 to produce LCP powder and obtain a porous body.

[0134] <Examples 4-6, Comparative Example 2>

[0135] In Examples 4-6 and Comparative Example 2, uniaxially oriented LCP particles (cylindrical particles with a diameter of 3-4 mm and a melting point of 340°C) were prepared as LCP raw materials. The LCP material was a copolymer of p-hydroxybenzoic acid and 4,6-hydroxynaphthoic acid. Except for changing the LCP raw material as described above, LCP powder was manufactured in the same manner as in Example 1. The average diameter of 100 LCP fibers contained in the LCP powder was measured to be 0.9 μm.

[0136] In addition, in Examples 4-6 and Comparative Example 2, the heating temperatures of the hot air-type non-oxidizing oven were 280°C, 290°C, 300°C, and 270°C, respectively. All other aspects were performed in the same manner as in Example 1 to obtain a porous body.

[0137] <Example 7>

[0138] In Example 7, uniaxially oriented LCP particles (cylindrical particles with a diameter of 3-4 mm and a melting point of 430°C) were prepared as the LCP raw material. The LCP material was a copolymer of p-hydroxybenzoic acid, terephthalic acid, and dihydroxybenzene. Except for changing the LCP raw material as described above, the LCP powder was manufactured in the same manner as in Example 1. The average diameter of the 100 LCP fibers contained in the LCP powder was measured to be 1.1 μm.

[0139] The LCP powder obtained above and the acrylic resin powder (average particle size: 2 μm) used as a resin binder were weighed and dispersed in a 50% by mass aqueous solution of ethanol as a dispersion medium at a volume ratio of 1:1, thereby forming a slurry. Next, the slurry-like resin mixture was processed in the same manner as in Example 1 to form a resin mixture felt.

[0140] The resin mixture felt obtained above was hot-pressed at 60°C and 0.6 MPa to produce a resin mixture membrane. Then, the resin mixture membrane was placed in a stainless steel drum and heated in the same hot-air non-oxidizing oven as in Example 1. Specifically, it was heated at 380°C for 60 minutes under a nitrogen flow. This yielded the porous body of Example 7.

[0141] <Example 8>

[0142] In Example 8, LCP powder and acrylic resin powder were weighed to achieve a volume ratio of 1:3. Otherwise, the process was the same as in Example 7 to obtain a porous body.

[0143] <Reference Example 1>

[0144] As a reference example 1, a unit area weight of 4g / m² is prepared. 2 Commercially available LCP meltblown nonwoven fabric.

[0145] [Observation of Porous Materials]

[0146] Figures 3-8 These are SEM images obtained by photographing the cross-sections of the porous bodies in Examples 1-3 and 7, Comparative Example 1, and Reference Example 1. (From...) Figures 3-8 As can be seen from the photographs, the porous body in the embodiment contains more fibers with larger diameters compared to the porous body in the comparative example, and the fibers are fused together. Furthermore, it can be seen that the porous body in Comparative Example 1 contains more fibers with smaller diameters, and the fusion of the fibers is insufficient. It should be noted that in Reference Example 1, the fibers are significantly thicker than those in the embodiment, and the shape of the pores is also simpler than in the embodiment. Additionally, when the porous body was obtained by heating at a temperature higher than the heating temperature of the above embodiment (above 280°C), it was confirmed that up to 310°C, which is 5°C lower than the melting point of the LCP raw material, it contained more fibers with larger diameters, and the fibers were fused together. However, it was confirmed that when the temperature exceeded 310°C, the fibers softened and the porous structure could not be maintained.

[0147] [Determination of pore distribution]

[0148] For each porous body of Examples 1-8, Comparative Examples 1-2, and Reference Example 1, the pore distribution was determined using a mercury porosimeter (MICROMETRICS, AutoPore V9605). The results are shown in Table 1 under “Average Pore Diameter (μm),” “Cumulative Pore Volume (mL / g),” and “Cumulative Pore Specific Surface Area (m²).” 2 / g)” column.

[0149] [ISO air permeability measurement]

[0150] For each porous body of Examples 1-8, Comparative Examples 1-2, and Reference Example 1, the ISO air permeability was measured using a Keller density meter (Keller air permeability tester manufactured by Yasuda Seiki Co., Ltd.). Air permeability is the average flow rate of air passing through per unit area, per unit pressure difference, and per unit time; a higher value means that air can pass through more easily. The ISO air permeability was measured according to JIS P8117:2009 "Paper and board paper - Test methods for air permeability and air resistance (intermediate zone) - Keller method". The results are shown in the "ISO air permeability (μm / Pa·s)" column of Table 1. As mentioned above, a higher ISO air permeability value means that air can pass through more easily, but if the value becomes too high, the density of the porous body may decrease, resulting in insufficient strength. Therefore, in this disclosure, 40 μm / Pa·s or less is considered good. It should be noted that, for Reference Example 1, the value was measured by overlapping 9 sheets of LCP meltblown nonwoven fabric.

[0151] [Determination of tensile strength]

[0152] For each porous body of Examples 1-8, Comparative Examples 1-2, and Reference Example 1, tensile strength was measured using a dynamic viscoelasticity tester (TA Instruments, RSA-G2). Specifically, for the porous body, a 5mm × 25mm test piece was used, and tension was applied at a clamping interval of 13mm and a tensile speed of 0.6mm / min. The tensile strength was calculated by dividing the load at cut by the cross-sectional area excluding the porous portion. The results are shown below. Figures 1-2 And Table 1 "Tensive Strength (N / mm)" 2 The value in Table 1 is the average of the n values ​​for each test piece. It should be noted that the n number for each test piece is 3.

[0153] surface

[0154]

[0155] like Figures 1-2 As shown in Table 1, the tensile strength of the porous bodies in Examples 1-8 is stronger than that in Comparative Examples 1-2. From... Figures 3-7The SEM images also show that the tensile strength increases as the fine fibers begin to fuse at a temperature approximately 60°C lower than the melting point of the LCP powder (255°C for Examples 1-3 and Comparative Example 1, and 280°C for Examples 4-6 and Comparative Example 2) and the amount of fiber fusion increases. It should be noted that in Reference Example 1, the average pore size is nearly 10 times larger, resulting in significantly poorer properties as a porous body, such as filtration characteristics.

[0156] Furthermore, it is known that the porous bodies in Examples 7 and 8 have extremely fine average pore sizes of less than 1.0 μm. Such porous bodies with fine average pore sizes are considered to have excellent strength and filtration properties.

[0157] Although Figures 1-2 As not shown in Table 1, but when a porous body is obtained by heating at a temperature higher than the heating temperature of the above-described embodiment, the tensile strength increases up to a temperature 20-30°C lower than the melting point of the LCP raw material. However, even when the temperature is increased to 5°C lower than the melting point of the LCP raw material, no further increase in tensile strength is observed. Furthermore, if the temperature exceeds 5°C lower than the melting point of the LCP raw material, ripples and large openings occur, making it impossible to maintain the film morphology, and therefore the tensile strength cannot be measured.

[0158] Experiment 2

[0159] <Example 9>

[0160] In Example 9, the same LCP powder as in Example 1 was used to form an LCP fiber mat through a coating process and a drying process.

[0161] First, a paste was prepared by dispersing the same LCP powder as in Example 1 in butanediol, which served as the dispersion medium.

[0162] Next, using a 160mm square metal plate, a paste-like LCP powder is coated onto the roughened surface of a 200mm square, 12μm thick electrolytic copper foil (manufactured by Furukawa Electric Industry Co., Ltd., FWJ-WS-12). Then, the electrolytic copper foil coated with the paste-like LCP powder is heated to 180°C on a hot plate, thereby vaporizing the butanediol used as a dispersion medium and drying the paste-like LCP powder on the electrolytic copper foil. This forms a thin LCP fiber mat on the electrolytic copper foil.

[0163] The aforementioned paste-like LCP powder is further coated onto the thin LCP fiber felt. This process is repeated in the same manner as drying the previously coated paste-like LCP powder, until the coated paste-like LCP powder is dried. By repeating the above coating and drying process multiple times, a weight per unit area of ​​15 g / m² is formed on the electrolytic copper foil. 2 LCP fiber felt.

[0164] Using the same hot-air non-oxidizing oven as in Example 1, the electrolytic copper foil with the above-mentioned LCP fiber felt formed was heated at 280°C for 60 minutes under a nitrogen flow. This resulted in a copper foil composite with a porous structure of approximately 70 μm thickness formed on a portion of one side of the copper foil.

[0165] <Example 10>

[0166] In Example 10, PTFE (amorphous, average particle size: 4.0 μm, melting point: 331 °C) was prepared as an additive.

[0167] A paste was prepared by dispersing PTFE and LCP powder (similar to that in Example 1) in butanediol as the dispersion medium. The mixing ratio of PTFE to LCP powder was 5:5 by volume. Other than the above, the manufacturing process was the same as in Example 9, resulting in a copper foil composite with a porous structure of approximately 50 μm thickness formed on a portion of one side of the copper foil.

[0168] <Example 11>

[0169] In Example 11, boron nitride powder (flaky, average particle size: 0.5 μm) was prepared as an additive.

[0170] A paste was prepared by dispersing boron nitride powder and LCP powder (similar to those in Example 1) in butanediol as the dispersion medium. The mixing ratio of boron nitride powder to LCP powder was 5:5 by volume. Other than the above, the manufacturing process was the same as in Example 9, resulting in a copper foil composite with a porous structure of approximately 50 μm thickness formed on a portion of one side of the copper foil.

[0171] [Observation of Copper Foil Composites]

[0172] In the copper foil composites of Examples 9-11, as described above, it is possible to form porous structures only on a portion of the copper foil surface, rather than the entire surface. Furthermore, even when the copper foil composites of Examples 9-11 are wound into a roll, the porous structures do not peel off from the copper foil, and warping or ripples do not occur.

[0173] [Waterproofing Test]

[0174] Water resistance tests were performed on Examples 9 and 10. Specifically, pure water or aqueous solutions of ethanol at various concentrations (50%, 60%, 70%, and 80% by mass) were added dropwise to the porous portions of each copper foil composite to confirm the presence or absence of adsorption.

[0175] In Example 9, it was confirmed that the material did not adsorb onto the porous body even when pure water was added, but it did adsorb onto the porous body when a 50% by mass ethanol aqueous solution was added. Similarly, adsorption was also confirmed in 60% by mass, 70% by mass, and 80% by mass ethanol aqueous solutions.

[0176] On the other hand, in Example 10, it was confirmed that the material did not adsorb onto the porous body even when pure water was added, nor did it adsorb onto the porous body in 50% by mass, 60% by mass, and 70% by mass aqueous ethanol solutions, but it adsorbed onto the porous body when 80% by mass aqueous ethanol solution was added.

[0177] The test results show that high water resistance can be achieved by mixing PTFE as an additive into LCP powder to form a porous body.

[0178] [Heat dissipation test]

[0179] Heat dissipation tests were conducted on Examples 9 and 11. Specifically, a copper plate was placed on a hot plate heated to 80°C, and the copper foil composites of Examples 9 and 11 were placed on it. The surface temperature was measured by thermal imaging.

[0180] The surface temperature of the copper foil composite in Example 11 was 5°C higher than that of the copper foil composite in Example 9. Based on this experimental result, it can be seen that heat dissipation can be imparted by mixing boron nitride powder as an additive into LCP powder to form a porous structure.

[0181] In addition, waterproofing and heat dissipation tests were conducted in this embodiment, but the results are not limited to waterproofing and heat dissipation; the porous body can be endowed with the functions of the additives.

[0182] In the above description of the embodiments, there are combinable configurations that can be combined with each other.

[0183] It should be understood that all aspects of the embodiments and implementations disclosed herein are merely illustrative and not limiting. The scope of this disclosure is not defined by the foregoing description, but by the scope of the claims, and is intended to include all modifications within the meaning and scope equivalent to the scope of the claims.

Claims

1. A porous body comprising liquid crystal polymer powder, The liquid crystal polymer powder comprises fibrous particles composed of liquid crystal polymers. The average diameter of the fibrous particles composed of liquid crystal polymer is less than 2 μm. The porous body has an average pore size of less than 10 μm, which is determined by mercury porosimetry. Furthermore, it has a strength of 25 N / mm. 2 The above tensile strength.

2. The porous body according to claim 1, wherein, Further includes additives.

3. The porous body according to claim 2, wherein, The additive is selected from at least one of polytetrafluoroethylene and nitride powder.

4. The porous body according to any one of claims 1 to 3, having an average pore size of less than 1.0 μm, wherein the average pore size is determined by mercury porosimetry.

5. A method for manufacturing a porous body, as described in claim 1, comprising: The dispersion process involves dispersing the liquid crystal polymer powder in a dispersion medium to obtain a paste or slurry-like form of the liquid crystal polymer powder. The felting process involves drying the paste-like or slurry-like liquid crystal polymer powder to form liquid crystal polymer fiber felt, and The heating process involves heating the liquid crystal polymer fiber felt to obtain a porous body; in, The heating temperature in the heating process is in the range of -60°C to -5°C, which is the melting point of the liquid crystal polymer powder.

6. The method for manufacturing a porous body according to claim 5, wherein, In the dispersion process, additives are further added to the liquid crystal polymer powder.

7. The method for manufacturing a porous body according to claim 5 or 6, wherein, In the felting process, the liquid crystal polymer powder in slurry form or a mixture of the liquid crystal polymer powder in slurry form and the additives is formed into the liquid crystal polymer fiber felt or the mixture felt by papermaking.

8. The method for manufacturing a porous body according to claim 5 or 6, wherein, The felting process includes a coating process of applying the paste-like liquid crystal polymer powder or the mixture to a substrate.

9. A method for manufacturing a porous body, the method for manufacturing a porous body according to claim 4, comprising: The dispersion process involves dispersing liquid crystal polymer powder and binder resin in a dispersion medium to obtain a paste or slurry-like resin mixture of the liquid crystal polymer powder and the binder resin. The felting process involves drying the paste-like or slurry-like resin mixture to form a resin mixture felt. The hot pressing process involves hot pressing the resin mixture felt to obtain a resin mixture film. A heating process is used to remove at least a portion of the adhesive resin contained in the resin mixture film by heating to obtain a porous body; in, The heating temperature in the heating process is in the range of -60°C to -5°C, which is the melting point of the liquid crystal polymer powder.

Citation Information

Patent Citations

  • Liquid crystal polyester fiber and production of liquid crystal polyester nonwoven fabric

    JP2000119952A

  • Heat-resistant nonwoven fabric

    JP2002061063A

  • Additive for polyolefin resin sheet and resin composition for the sheet compounded with the same

    JP2003026866A

  • Wet-laid nonwoven fabric

    JP2003129392A

  • Liquid crystal polyester melt blow nonwoven fabric and method for producing the same

    JP2005120535A